(untitled) (ENTHYMEMA, 2019)
In The Book of Dolores, a series of self-portraits in photography and drawings with accompanying text, William T. Vollmann pictures himself as a cross-dresser. He uses various techniques that emphasize the pictorial approach of photography, to create an uncanny icon of femininity. As an attempt to reach the other side, not just of gender, but of life, his negative prints in particular seem to reveal a ghostly presence. In TheBook of Dolores, una serie di autoritratti fotografici e disegnati e accompagnati da un testo scritto, William T. Vollmann si ritrae come un travestito. Utilizza diverse tecniche che enfatizzano l’approccio pittorialista alla fotografia per creare un’icona perturbante della femminilità. Tentativi di raggiungere l’altro lato, non solo del genere, ma anche della vita, i suoi negativi, in particolare, sembrano rivelare una presenza spettrale.